Does Company Size Moderate the Influence of Ownership Managerial on Profit Growth in Indonesian Retail Companies? - Nik Amah (FISCAL: Jurnal Akuntansi dan Perpajakan, 2024)
Profit growth is an indicator of the increase in a company's net profit from the previous period which is useful for giving investors an idea of how good the company's condition is in generating profits. The aim of this research is to determine the moderating role of company size on the influence of managerial ownership on profit growth. This research uses a quantitative approach with a moderated regression model. The sample used comes from annual financial reports for the period 2017 to 2022 which are listed on the Indonesian Stock Exchange. The sampling technique was carried out using a purposive sampling method to obtain 71 retail company financial report data. Data analysis uses multiple linear analysis and moderated regression analysis (MRA). The research results show that managerial ownership has a positive and significant effect on profit growth, company size cannot moderate the effect of managerial ownership on profit growth, but it is proven to be an independent variable that has a positive effect on profit growth. The conclusion of the research is that the type of moderation that occurs is a predictor of moderation. This research is expected to provide scientific insight into company profit growth.